2007
DOI: 10.1038/sj.jid.5700779
|View full text |Cite
|
Sign up to set email alerts
|

Dermokine: An Extensively Differentially Spliced Gene Expressed in Epithelial Cells

Abstract: Studies performed to discover genes overexpressed in inflammatory diseases identified dermokine as being upregulated in such disease conditions. Dermokine is a gene that was first observed as expressed in the differentiated layers of skin. Its two major isoforms, alpha and beta, are transcribed from different promoters of the same locus, with the alpha isoform representing the C terminus of the beta isoform. Recently, additional transcript variants have been identified. Extensive in silico analysis and reverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 13 publications
2
34
1
Order By: Relevance
“…Dmkn encodes a secreted protein of unknown function that is highly expressed in the spinous and granular layers of stratified epithelia (Matsui et al, 2004) but is also expressed in the gut, lung, breast, liver and pancreas (Naso et al, 2007). The wide expression profile of Dmkn is reminiscent of that for Perp, which is expressed in stratified epithelia as well as in the heart, forestomach, submandibular gland and thymus (Ihrie et al, 2005).…”
Section: Perp and The Regulation Of Gene Expressionmentioning
confidence: 99%
“…Dmkn encodes a secreted protein of unknown function that is highly expressed in the spinous and granular layers of stratified epithelia (Matsui et al, 2004) but is also expressed in the gut, lung, breast, liver and pancreas (Naso et al, 2007). The wide expression profile of Dmkn is reminiscent of that for Perp, which is expressed in stratified epithelia as well as in the heart, forestomach, submandibular gland and thymus (Ihrie et al, 2005).…”
Section: Perp and The Regulation Of Gene Expressionmentioning
confidence: 99%
“…2A, exposure of keratinocytes to dermokine-b for 24 h stimulated its gene expression in a dose-dependent manner, whereas no significant change of involucrin expression was observed. A secreted form of dermokine-b consists of amino-terminus globular (Glo1), coiled-coil collagen-like (Coil), keratin-like (Ker), spacer (Spa) and carboxyl-terminus globular domain (Glo2) [6]. To define the active regions of dermokine-b to stimulate its gene expression, dermokine-b deletion mutants were prepared, and incubated with keratinocytes at a dose of 3 lg/ml (Fig.…”
Section: Carboxyl-terminus Domain Of Dermokine-b Exhibits Functional mentioning
confidence: 99%
“…Unlike the c and d isoforms, dermokine-a is also a secreted protein that contains the same carboxyl-terminus globular domain as dermokine-b [4,6]. We and others have suggested that the expressions of both dermokine-b and -a were coordinately regulated [4,9], implying the additional involvement of dermokine-a in keratinocyte differentiation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The mouse SSC locus displays the same genomic organization as that of humans, with Sbsn and Krtdap flanking Dmkn, in the same orientation. Dmkn spans 22 exons and transcripts belonging to the a, b and c isoforms have been described, but no messengers coding putative d isoforms (Matsui et al, 2004;Moffatt et al, 2004;Naso et al, 2007). Here, we performed an in-depth characterization of the Dmkn transcripts expressed in the mouse skin.…”
Section: Introductionmentioning
confidence: 99%